Program Student Visit dalam Pameran Plastics and Rubber Indonesia 2023 PT Pamerindo Indonesia - Syam, Hilmi Sofya Angelina; Setyawan, Heri (Bisnis Event, 2025)
This study examines the impact of the Student Visit Program on active learning among university students attending the "Plastics & Rubber Indonesia 2023" exhibition. The program aims to bridge the gap between academia and industry by providing students with firsthand exposure to industrial practices and innovations in the plastics sector. A qualitative research method with a descriptive approach was utilized to explore the preparation and execution of the program. The results reveal that the program significantly enhances students' practical understanding of industrial applications, motivating them to engage more actively in their learning process. Challenges such as scheduling conflicts and communication issues were identified, but overall, the program was successful in achieving its educational objectives.